Multiphase Interfacial Regulation Based on Hierarchical Porous Molybdenum Selenide to Build Anticorrosive and Multiband Tailorable Absorbers - Zhao, Tianbao; Jia, Zirui; Liu, Jinkun; Zhang, Yan; Wu, Guanglei; Yin, Pengfei (Nano-Micro Letters, 2023)
Electromagnetic wave (EMW) absorbing materials have an irreplaceable position in the field of military stealth as well as in the field of electromagnetic pollution control. And in order to cope with the complex electromagnetic environment, the design of multifunctional and multiband high efficiency EMW absorbers remains a tremendous challenge. In this work, we designed a three-dimensional porous structure via the salt melt synthesis strategy to optimize the impedance matching of the absorber. Also, through interfacial engineering, a molybdenum carbide transition layer was introduced between the molybdenum selenide nanoparticles and the three-dimensional porous carbon matrix to improve the absorption behavior of the absorber. The analysis indicates that the number and components of the heterogeneous interfaces have a significant impact on the EMW absorption performance of the absorber due to mechanisms such as interfacial polarization and conduction loss introduced by interfacial engineering. Wherein, the prepared MoSe2/MoC/PNC composites showed excellent EMW absorption performance in C, X, and Ku bands, especially exhibiting a reflection loss of − 59.09 dB and an effective absorption bandwidth of 6.96 GHz at 1.9 mm. The coordination between structure and components endows the absorber with strong absorption, broad bandwidth, thin thickness, and multi-frequency absorption characteristics. Remarkably, it can effectively reinforce the marine anticorrosion property of the epoxy resin coating on Q235 steel substrate. This study contributes to a deeper understanding of the relationship between interfacial engineering and the performance of EMW absorbers, and provides a reference for the design of multifunctional, multiband EMW absorption materials. Highlights: 1 The hierarchical porous structure is regulated by various species of PVP to achieve impedance matching. 2 Interfacial engineering boosts conductivity and constructs a multiband (C, X, Ku) tunable electromagnetic wave absorber. 3 Hierarchical porous molybdenum selenide/epoxy coating exhibits marine anticorrosion capability.